Ligand Evolution in the Photoactivatable Platinum(IV) Anticancer Prodrugs - Huang, Jingjing; Ding, Weize; Zhu, Xingfan; Li, Bingbing; Zeng, Fangang; Wu, Kui; Wu, Xiaoqin; Wang, Fuyi (Frontiers in Chemistry, 2022)
Photoactivatable Pt(IV) anticancer prodrugs with the structure of [PtIV(N1)(N2)(L1)(L2)(A1)(A2)], where N1 and N2 are non-leaving nitrogen donor ligands, L1 and L2 are leaving ligands, and A1 and A2 are axial ligands, have attracted increasing attentions due to their promising photo-cytotoxicity even to cisplatin-resistant cancer cells. These photochemotherapeutic prodrugs have high dark-stability under physiological conditions while they can be activated by visible light restrained at the disease areas, as a consequence showing higher spatial and temporal controllability and much more safety than conventional chemotherapy. The coordinated ligands to Pt center have been proved to be pivotal in determining the function and activity of the photoactivatable Pt(IV) prodrugs. In this review, we will focus on the development of the coordinated ligands in such Pt(IV) prodrugs, discuss the effects of diverse ligands on their photochemistry and photoactivity as well as the future evolution directions of the ligands. We hope this review can help to facilitate the design and development of novel photoactivatable Pt(IV) anticancer prodrugs.